A Rare Case of Castleman Disease Presenting as an Ovarian Tumor. (July 2021) - D'Antonio, Antonio; Caleo, Alessia; Addesso, Maria; Caputo, Alessandro; Fraggetta, Filippo; Ponzoni, Maurilio
Abstract : Castleman disease (CD) is a rare lymphoproliferative disorder of unknown etiology. Its most common location is the mediastinum, but many other sites have been reported. We report a case of primary CD of the ovary, a rare localization with only 2 cases including the present case described in the world literature to date. A 58-yr-old woman who initially presented with abdominal pain underwent computed tomography scan which showed bilateral well-circumscribed solid adnexal masses. Because an ovarian bilateral tumor was suspected the patient was treated with a hysterectomy and bilateral salpingo-oophorectomy and the histopathologic examination confirmed the diagnosis of CD hyaline-vascular type of the right ovary associated with a contralateral fibroma. Three years after surgery the patient is alive and well and shows no signs of recurrent disease. The occurrence of this rare presentation of CD is the subject of this report. The problems of differential diagnosis with the most frequent lesions of the female pelvis are also discussed.